Sexuality to debate. Transformations, tensions and continuities in recent Costa Rican history - Fernández Carvajal, Doris (2020)
This article refers to some discussions that have taken place in Costa Rica in the last 50 years, regarding issues related to sexuality. Events that marked the course of history in this field, its repercussions and the challenges they generated were analyzed. Several of these disputes revolve around sexual education, sexually transmitted diseases, family planning, overpopulation, abortion and other relevant issues. In these discussions, different social actors were highlighted, with multiple approaches or visions that were often opposed and whose interventions raised tensions in the national political environment and sometimes weakened state initiatives. The review and analysis of the information was carried out based on national newspapers, scientific research, project reports, books and academic articles, which were produced between 1965 and 2019. The analyzes carried out lead to affirm that the discussions in sexuality and reproduction have had a leading place in the country’s vision of development, hence the importance of contextualizing the social dynamics linked to them and the implications they have in people’s lives.